COST531 project: Study of the advanced materials for lead free soldering - Kroupa A.; Dinsdale A.T.; Watson A.; Vrestal J.; Zemanova A. (Journal of Mining and Metallurgy. Section B: Metallurgy, 2007)
The COST 531 [1] project runt in the years 2002-2007, and dealt with the materials suitable for lead-free soldering. The main aim was to increase the basic knowledge on possible alloy systems that were used or planned to be used as lead-free solder materials and offer scientific information about these materials in order to replace the currently used lead-containing solders. The databases of materials and thermodynamic properties are one of the expected results and the basic features and properties of the thermodynamic database, allowing to model phase diagrams in multicomponent systems, are described in following paper.